The effects of rivaroxaban, an oral anticoagulant, on human IVD primary cultures - Çalışkan, Tezcan; Akalan, Hande; Yılmaz, İbrahim; Karaarslan, Numan; Yaşar Şirin, Duygu; Özbek, Hanefi (Termedia Publishing House Ltd, 2022)
Introduction: The present study aimed to investigate the potential effects of rivaroxaban, an oral anticoagulant that inhibits the effects of factor Xa, on intact intervertebral disc tissue cells and the extracellular matrix (ECM). Material and methods: Rivaroxaban was applied to primary human cell cultures prepared from tissues of the intervertebral disc. Comparative molecular analyses were performed on non-drug-treated control group samples. Descriptive statistics were presented as the mean +/- standard deviation. An analysis of variance test was performed to determine whether there were significant differences in the mean across the groups. When differences across groups were observed, Tukey's honestly significant difference post-hoc test was used for multiple pairwise comparisons. The significance of the obtained data was determined statistically. The alpha significance value was < 0.05. Results: The cells in the control group and in the rivaroxaban-treated group were viable, healthy, and proliferated (p < 0.05). However, the expression levels of the chondroadherin gene (CHAD), cartilage oligo matrix protein (COMP), matrix metalloproteinase (MMP)-13, and MMP-19 genes were changed (p < 0.05). Conclusions: Although rivaroxaban does not suppress cell proliferation due to morphological, biological, and biochemical changes in the intervertebral disc tissue, it may change the expression of genes that are related to ECM maintenance.
Keywords: Cartilage Oligo Matrix Protein; Chondroadherin Gene; Cytotoxicity; Intervertebral Disc Cells; Matrix Metalloproteinases; Nucleus Pulposus; Rivaroxaban